Detection of a neonatal human rotavirus strain with VP4 and NSP4 genes of porcine origin - Mascarenhas, Joana D'Arc Pereira (2007)
A human rotavirus strain (NB-150) was detected in stool samples from a neonate hospitalized for mild/moderate community-acquired diarrhoea. This baby lived in the outskirts of Belém, Brazil, under poor sanitation conditions. The NB-150 strain displayed a typical long electrophoretic pattern with 11 gene segments. It had two VP7 alleles, G1 and G4, and belonged to VP6 subgroup II. Aclose relatedness with human rotaviruses was shown for VP7 alleles: G1 (96.9û100 per cent) similarity at the amino acid level) and G4 (97.1û100 per cent similarity at the amino acid level). As for VP6, 95.1û97.5 per cent similarity at the amino acid level was noted. VP8* and NSP4 genes showed a close relatedness with those of porcine rotavirus strains, as follows: VP8* (95.0 per cent similarity at the amino acid level) and NSP4 (93.7û96.0 per cent similarity at the amino acid level). This is believed to be the first report in Brazil of a rotavirus infection involving a strain with G1 and G4 alleles, with VP8* and NSP4 genes of porcine origin. These findings strongly suggest the occurrence of interspecies transmission.